Efficacy of Proliferation of HeLa Cells under Three Different Low-Intensity Red Lasers Irradiation - H. Q. Yang; Y. H. Wang; J. X. Chen; X. G. Chen; Y. M. Huang; H. Li; S. S. Xie; L. Q. Zheng (International Journal of Photoenergy)
This study was intended to compare the efficacy of proliferation of HeLa cells under three different low-intensity laser irradiation (LIL), that is, 633 nm, 658 nm, and 785 nm. The time-dependent responses of proliferation of HeLa cells after the red laser irradiation and the influence of fetal bovine serum (FBS) at 1%, 2%, 5%, or 10% on the proliferation of cells were also investigated. The results indicated that the proliferation of HeLa cells in 10% FBS was in proliferation-specific homeostasis (PSH) so that it was not modulated with LIL; the proliferation in FBS at 1%, 2%, or 5% was far from PSH so that it may be wavelength dependently modulated with LIL, and the maximum proliferation promotion was conducted with LIL at 633 nm amongst the three different LIL. It was concluded the wavelength-dependent photobiomodulation of LIL on proliferation of HeLa cells may be homeostatic.